2016
DOI: 10.3847/0004-637x/831/2/186
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal Solar Euv Intensity Fluctuations and Their Implications for Coronal Heating Models

Abstract: We investigate the scaling properties of the long-range temporal evolution and intermittency of Atmospheric Imaging Assembly/Solar Dynamics Observatoryintensity observations in four solar environments: anactive region core, a weak emission region, and two core loops. We use two approaches: the probability distribution function (PDF) of time series incrementsand multifractal detrended fluctuation analysis (MF-DFA). Noise taints the results, so we focus on the 171 Å waveband, which has the highest signal-to-n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…in studying turbulent flows). In astrophysics, it has been used, for example, in the study of the distribution of galaxies (Mandelbrot 1989;Borgani et al 1993;Pan & Coles 2000;de La Fuente Marcos & de La Fuente Marcos 2006), gamma-ray burst time series (Meredith et al 1995), and solar activity (Wu et al 2015;Cadavid et al 2016;Maruyama et al 2017).…”
mentioning
confidence: 99%
“…in studying turbulent flows). In astrophysics, it has been used, for example, in the study of the distribution of galaxies (Mandelbrot 1989;Borgani et al 1993;Pan & Coles 2000;de La Fuente Marcos & de La Fuente Marcos 2006), gamma-ray burst time series (Meredith et al 1995), and solar activity (Wu et al 2015;Cadavid et al 2016;Maruyama et al 2017).…”
mentioning
confidence: 99%
“…This introduces correlations in the signals, which is at the center of what our analysis has uncovered. A more complex model based on impulsive heating by Pauluhn & Solanki (2007) was used to interpret the multiscaling properties of intensity fluctuations of the AIA 171 Å signals in an active region core and coronal loops (Cadavid et al 2016). In this case the intensity time series result from a sequence of "nanoflares" (exponential impulses as described above), which occur at each observational time step with a certain probability P f , a time scale T , and an amplitude E sampled from a power law distribution with scaling exponent α E > 2.…”
Section: Summary and Discussion Of Resultsmentioning
confidence: 99%
“…exponents for some turbulence models via a relation with the second-order structure function H = ξ(2)/2 (e.g.,Davies et al 1994). Some examples are: 0.33 (Kolmogorov), 0.35 (She-Leveque), 0.37 (Müller-Biskamp) Cadavid et al (2016). found that 171 Å emission in two hot coronal loops in an active region core had generalized Hurst exponents of 1.34 and 1.41 (H = 0.34, 0.41), which together with other diagnoses suggested a turbulent process.…”
mentioning
confidence: 95%
“…Nevertheless, they are designed for providing an astute fitting scheme to turbulence data, and they all have indeed been successfully adapted and applied to solar wind turbulence (Bruno 2019). The multifractal phenomenology can also be applied for studying the radiation fields emitted by multiscale astrophysical objects observed at high resolution (Yahia et al 2021), including light emitted by the Sun in different energy ranges (Cadavid et al 2016). It is equally fruitful to use it in a Lagrangian perspective, in order to study the structure of the Lagrangian fields: the Eulerian fields evaluated along fluid particle trajectories.…”
Section: Eulerian Descriptionmentioning
confidence: 99%